New development: The emerging role of a 'learning partner' relationship in supporting public service reform. Issue 8 (17th November 2021) - Hesselgreaves, Hannah; French, Max; Hawkins, Melissa; Lowe, Toby; Wheatman, Amy; Martin, Mike; Wilson, Rob
IMPACT: This article describes why managers of public services who are engaged in reform should consider engaging in learning partnerships. The authors explain how this emerging approach provides important sources of reflexive practice to members of partnerships, including policy-makers, consulting firms, and academia; they show how these sectors can collaborate to build learning capacity across multiple stakeholders; as well as the dilemmas and dualisms involved. ABSTRACT: As public services face the limits of existing approaches to public management, emerging practices are highlighting the importance of continuous learning and service reform. While many approaches, methods and aids for learning exist, managers embracing complexity are making use of relational resources to scaffold their learning capacity-building. This article introduces the idea of 'learning partnerships': a set of nested learning relationships between public managers, consultants, and researchers and academics, which extends the literature on academic–practitioner collaborations and builds a relational mechanism for learning into the action learning action research (ALAR) and learning organization genres.